2014
DOI: 10.1371/journal.pone.0084832
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Extension Improves Neurocognitive Functions in Chronically Sleep-Deprived Obese Individuals

Abstract: BackgroundSleep deprivation and obesity, are associated with neurocognitive impairments. Effects of sleep deprivation and obesity on cognition are unknown, and the cognitive long-term effects of improvement of sleep have not been prospectively assessed in short sleeping, obese individuals.ObjectiveTo characterize neurocognitive functions and assess its reversibility.DesignProspective cohort study.SettingTertiary Referral Research Clinical Center.PatientsA cohort of 121 short-sleeping (<6.5 h/night) obese (BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
2
23
0
2
Order By: Relevance
“…Our finding that sleep extension (objectively measured) is feasible in real life settings is consistent with two recent reports where extending sleep duration (assessed by self-reported sleep diaries) had beneficial effects on neurocognitive function in habitually short sleeping healthy and obese individuals (16, 17). On average, our participants obtained 1.6 hours more sleep with extended bedtimes, which is comparable in magnitude to the difference in sleep duration reported in prior studies as having adverse effects of sleep restriction on diabetes and obesity risk (18-21).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that sleep extension (objectively measured) is feasible in real life settings is consistent with two recent reports where extending sleep duration (assessed by self-reported sleep diaries) had beneficial effects on neurocognitive function in habitually short sleeping healthy and obese individuals (16, 17). On average, our participants obtained 1.6 hours more sleep with extended bedtimes, which is comparable in magnitude to the difference in sleep duration reported in prior studies as having adverse effects of sleep restriction on diabetes and obesity risk (18-21).…”
Section: Discussionsupporting
confidence: 91%
“…One approach to improving overnight sleep is to extend total time in bed or adjust sleep/nighttime habits (e.g., by routinizing bedtimes). These behavior-based sleep extension manipulations have been linked to positive cognitive outcomes in adolescents, young adults, and middle-aged adults (e.g., Dewald-Kaufmann, Oort, & Meijer, 2013; Lucassen et al, 2014; Mah, Mah, Kezirian, & Dement, 2011; but see Sadeh, Gruber, & Raviv, 2003). One study is suggestive of a similar benefit in healthy older adults (Klerman & Dijk, 2008), but this study did not control for practice effects (Shipstead, Redick, & Engle, 2012).…”
Section: Nocturnal Sleep Interventions For Cognitionmentioning
confidence: 99%
“…Furthermore, clinical trials with adult samples have demonstrated that extending sleep over six weeks to twelve months in natural environments is feasible (Cizza et al, 2011; Leproult, Deliens, Gilson, & Peigneux, 2015). Further, in non-obese adults, the additional sleep contributed to improved insulin sensitivity and glucose levels (Leproult et al, 2015) as well as neurocognition (Lucassen et al, 2014). …”
Section: Experimental Manipulation Of Sleepmentioning
confidence: 99%